Investigation of serum vaspin, visfatin, chemerin and IL-18 levels in migraine patients - Ahmet Dönder; Vugar Cafer; Ahmet Yilmaz; Hamza Aslanhan; Adalet Arikanoğlu (Arquivos de Neuro-Psiquiatria)
Abstract Background: Migraines are headaches caused by changes in the trigeminovascular metabolic pathway. Migraine headache attacks are associated with neurovascular inflammation, but their pathophysiological mechanisms have not been fully explained. Objective: To investigate the relationship between serum vaspin, visfatin, chemerin and interleukin-18 (IL-18) levels and the frequency of attacks in migraine headache. Methods: Three groups were established: migraine with aura (n = 50), migraine without aura (n = 50) and control group (n = 50). The migraine diagnosis was made in accordance with the International Classification of Headache Disorders-III beta diagnostic criteria. The analyses on serum vaspin, visfatin, chemerin and IL-18 levels were performed using the enzyme-linked immunosorbent assay method. Results: The serum vaspin, visfatin, chemerin and IL-18 levels were found to be significantly higher in the migraine patients than in the control group (p < 0.01). No statistically signiﬁcant differences in serum vaspin, visfatin, chemerin and IL-18 levels were found among the migraine patients during attacks or in the interictal period (p>0.05). The serum visfatin and chemerin levels of the migraine patients were positively correlated with their serum IL-18 levels (p < 0.01), while their serum chemerin and visfatin levels were positively correlated with their serum vaspin levels (p < 0.05). Conclusions: This study showed that these biomarkers may be related to migraine pathogenesis. Nonetheless, we believe that more comprehensive studies are needed in order to further understand the role of vaspin, visfatin, chemerin and IL-18 levels in the pathophysiology of migraine headaches.